Nutritional Status of Under-five Children Living in an Informal Urban Settlement in Nairobi, Kenya - Olack, Beatrice; Burke, Heather; Cosmas, Leonard; Bamrah, Sapna; Dooling, Kathleen; Feikin, Daniel R; Talley, Leisel E; Breiman, Robert F (Journal of Health, Population and Nutrition, 2011)
Malnutrition in sub-Saharan Africa contributes to high rates of childhood morbidity and mortality. However, little information on the nutritional status of children is available from informal settlements. During the period of post-election violence in Kenya during December 2007–March 2008, food shortages were widespread within informal settlements in Nairobi. To investigate whether food insecurity due to post-election violence resulted in high prevalence of acute and chronic malnutrition in children, a nutritional survey was undertaken among children aged 6-59 months within two villages in Kibera, where the Kenya Medical Research Institute/Centers for Disease Control and Prevention conducts population-based surveillance for infectious disease syndromes. During 25 March–4 April 2008, a structured questionnaire was administered to caregivers of 1,310 children identified through surveillance system databases to obtain information on household demographics, food availability, and child-feeding practices. Anthropometric measurements were recorded on all participating children. Indices were reported in z-scores and compared with the World Health Organization (WHO) 2005 reference population to determine the nutritional status of children. Data were analyzed using the Anthro software of WHO and the SAS. Stunting was found in 47.0% of the children; 11.8% were underweight, and 2.6% were wasted. Severe stunting was found in 23.4% of the children; severe underweight in 3.1%, and severe wasting in 0.6%. Children aged 36-47 months had the highest prevalence (58.0%) of stunting while the highest prevalence (4.1%) of wasting was in children aged 6-11 months. Boys were more stunted than girls (p<0.01), and older children were significantly (p<0.0001) stunted compared to younger children. In the third year of life, girls were more likely than boys to be wasted (p<0.01). The high prevalence of chronic malnutrition suggests that stunting is a sustained problem within this urban informal settlement, not specifically resulting from the relatively brief political crisis. The predominance of stunting in older children indicates failure in growth and development during the first two years of life. Food programmes in Kenya have traditionally focused on rural areas and refugee camps. The findings of the study suggest that tackling childhood stunting is a high priority, and there should be fostered efforts to ensure that malnutrition-prevention strategies include the urban poor. Key words: Child nutrition; Child nutrition disorders; Child nutritional status; Cross-sectional studies; Food security; Informal settlement; Slums; Kenya DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8451 JHPN 2011; 29(4): 357-363